State Bankruptcy Law and Entrepreneurship: Evidence from a Border Analysis - Amanda Ross; Shawn Rohlin (European Regional Science Association (ERSA), 2013)
This paper examines how differences in state bankruptcy laws, specifically the amount of the homestead exemption, affect business location decisions. We expand upon the literature by narrowing the geographic scope and focus on the amount of entrepreneurial activity within a few miles of the state boundary. By including only these border areas, we are more effectively able to control for unobserved local attributes, which are important determinants of business location decisions. Findings indicate that an increase in a state?s homestead exemption attracts new businesses to that locality. In addition, we do not find that a more generous homestead exemption has a negative impact on existing businesses. Our results suggest that bankruptcy law is an important policy tool that state governments can use to attract new businesses, without experiencing an adverse effect on existing enterprises.
Keywords: 330; bankruptcy; entrepreneurship; borders